Diffusion-weighted Magnetic Resonance Imaging: What Makes Water Run Fast or Slow? - Fornasa, Francesca
Diffusion-Weighted Magnetic Resonance Imaging (DWI) obtains information useful in diagnosing several diseases through the measurement of random, Brownian diffusion of water molecules in tissues. This pictorial essay illustrates the main factors, i.e., ratio between the volume occupied by cells and the extracellular space, composition of the extracellular space, and temperature, that determine the rate of the water diffusion. The mechanism through which these influencing factors affect water diffusion is explained. Clinical and experimental examples, derived both from physiology and from non-human models, are described.